Gender - Based Violence in Education: A Systematic Review of Factors, Forms and Prevention - Farid Fauzi (The Future of Education Journal, 2025)
Gender - Based Violence (GBV) in educational institutions is a serious problem that impacts the safety, psychological health and academic achievement of students. This study aims to systematically examine the causes, forms and efforts to address GBV in the educational context using the Systematic Literature Review (SLR) method. The literature search process was conducted in reputable scientific databases using keywords relevant to GBV, education  and power relations. Selected articles were selected based on inclusion and exclusion criteria, then analyzed thematically to identify patterns and trends in research findings. The results of the study indicate that the main factors of GBV in educational institutions include rigid gender stereotypes and norms, patriarchal culture, unequal power relations, dysfunctional family backgrounds, substance abuse and the influence of the internet and technology. The most frequently reported forms of violence include physical, verbal, psychological, sexual and symbolic violence that occurs both in person and through online media. The impact of this violence not only reduces students' sense of security and psychological well-being but also negatively affects attendance and academic achievement. Therefore, this study emphasizes the importance of a comprehensive response strategy through gender equality education, strengthening institutional policies, increasing educator capacity  and providing support systems and safe spaces for victims. These findings are expected to inform the development of more inclusive educational policies and practices free from GBV.